PLANNING AND SUSTAINABILITY TRAJECTORIES IN A RAPIDLY GROWING METROPOLIS: ISTANBUL - Ozugul, Mehmet Doruk; Cengiz, Huseyin (EMERALD GROUP PUBLISHING LTD, 2011)
Since sustainability is an optimization between physical (both natural and man-made), economic and social dimensions of development and conservation, plans, policies and applications in rapidly growing metropolises play a pivotal rote for manifestation of this challenge. This article consists of three inter-related parts. First, core issues of a sustainable master plan are identified from a wide range of readings of the current literature. Second, as one of the most populated and rapidly growing metropolises of the world, Istanbul's master plans between 1980 and 2009 are evaluated in terms of their convenience to the core issues of sustainability. Finally in context of sustainability, the actual position of Istanbul is criticized on the basis of some additional qualitative and quantitative data. The above-mentioned core issues are: urban compactness, sustainable transportation, conservation of historical heritage, a clear balance between nature and man-made environments / permeability of the built environment (for natural corridors), protection of vulnerable natural assets, rehabilitation of natural ecosystems, natural resource management, a place-based economy, control of the population pressure over the environment, (low-income) housing, provision of social equity and cultural diversity. Consideration of these issues aids in analyzing the main policies of the three master plans (1980, 1995 and 2009) in context of sustainability on the one hand and picturing today's Istanbul, on the other. In fact the gap between planning and the actual situation is a characteristic problem for developing countries where illegal developments are almost legitimate. In these countries, planning also suffers from guiding development in sustainable terms due to lack of institutional capacity, participation and inadequate legal arrangements. In brief, this article focuses on the reasons and consequences of such a gap in the case of a rapidly growing metropolis.
Keywords: Sustainability; Sustainable Urban Development; Urban Planning; PREFERENCES; Architecture; Environmental Sciences & Ecology; Urban Studies